Bacteriophages Reduce Pathogenic Escherichia coli Counts in Mice Without Distorting Gut Microbiota - Dissanayake, Upuli; Ukhanova, Maria; Moye, Zachary Daniel; Sulakvelidze, Alexander; Mai, Volker (Frontiers in Microbiology, 2019)
We performed a study to (i) investigate efficacy of an Escherichia coli/Salmonella spp./Listeria monocytogenes-targeting bacteriophage cocktail (tentatively named F.O.P.) to reduce a human pathogenic E. coli strain O157:H7 in experimentally infected mice, and (ii) determine how bacteriophages impact the normal gut microbiota when compared with antibiotic therapy. A total of 85 mice were inoculated with E. coli O157:H7 strain Ec231 (nalidixic acid resistant (NalAcR)) via oral gavage, and were randomized into six groups separated into three categories: 1st category received PBS or No phage/No PBS (control), 2nd category received either F.O.P., F.O.P. at 1:10 dilution, or the E. coli phage component of F.O.P (EcoShield PX™), and 3rd category received the antibiotic ampicillin. All therapies were administered twice daily for four consecutive days, except ampicillin which was administered twice on day zero before and after bacterial challenge. Fecal samples collected at Days 0, 1, 2, 3, 5, and 10. Samples were homogenized and plated on LB plates supplemented with NalAc to determine viable Ec231 counts. Individual weights were recorded at every fecal sample collection for trend analysis. qPCR was performed using specific E. coli primers to quantify the number of E. coli genome copies. Microbiota community profiles were analyzed using Denature Gradient Gel Electrophoresis (DGGE) and 16S rRNA sequencing. F.O.P. significantly (P< 0.05) reduced E. coli pathogen counts by more than 55% with a similar reduction observed with ampicillin therapy. Greater initial weight-loss occurred in mice treated with ampicillin (-5.44%) compared to other treatment groups. No notable changes in the gut microbiota profiles were observed for control and F.O.P. groups. In contrast, the antibiotic group displayed noticeable distortion of the gut microbiota composition, only partially returning to normal by Day 10. In conclusion, we found that F.O.P. administration was effective in reducing viable E. coli in infected mice with a similar efficacy to ampicillin therapy. However, the F.O.P. bacteriophage preparation had less impact on the gut microbiota compared to ampicillin.